KORUPSI: SUATU KAJIAN ANALISIS DI NEGARA MAJU DAN NEGARA BERKEMBANG - Yeni Sri Lestari (Prodi Sosiologi FISIP Universitas Teuku Umar, 2017)
This article analyzes the history and development of corruption in some countries, where corrupt practices are not a new problem but it has long been emerging and eternal to this day. The practice of corruption is a crucial issue for the development of a nation state, especially affecting the welfare of citizens in obtaining their rights in a prosperous and prosperous state life. This study is a reference to the increasing complexity of corrupt practices in various societies and sectors of society. Therefore, the discussion in this article examines how corruption is in developing countries and developed countries. This study found that corruption is a classic phenomenon that has occurred since a long time, starting from the period before the development of the modern world that is in the kingdom period in developing countries and in times of war in Western countries. The form of corruption practices is inseparable from human behavior that always feel dissatisfied with what they have. At the end of the study, this article explains that there is a very significant difference to corrupt practices in developing countries with developed countries, especially from the perspective of society and how to overcome corruption practices in both countries, it also explains the impact that arises in both countries corrupt practices. Keywords : Corruption, Third Country, and First Country